Mesoscale and Microphysical Features of Frontal Rainbands in the Deep Depression of Explosive Cyclone Type over the Antarctic Peninsula - S. V. Krakovskaia; A. M. Pirnach (Ukrainian Antarctic Journal, 2003)
The study is focused on the numerical simulation of frontal rainbands associated with a deep depression of the explosive cyclone type, moved over the Antarctic Peninsula from the South Pacific and caused severe weather and heavy precipitation 01-02.04.98. To study the formation and development of supercooled frontal rainbands, the adaptation of previously worked out numerical models to the specific region with limited initial data both for the simulation and verification of the model outputs has been performed. Outputs of 3-D novacasting limited area model (LAM) based on rawinsonde data of Bellingshausen station are used as initial data for 1-D forecasting microphysical model. A set of equations is used to simulate the evolution of the processes of condensation, nucleation, freezing, sedimentation, accretion, collection, etc. Thermodynamical conditions in the troposphere are continuously updated as the system moved over the initial point in 1-D simulation. Two tracks via the frontal rainbands are studied. The study shows that at the same thermodynamic conditions the liquid phase of the precipitation formed only by coagulation processes less depends on the concentrations, while the solid phase changes dramatically when the concentrations varying, in particular, over the Antarctic Peninsula. The study has pointed extreme values of cloud microphysical empirical parameters and showed that frontal clouds moved from the Pacific to the West Antarctic undercertain conditions can accumulate the huge reserve of precipitable moisture that could result in heavy rain and snowfalls.